K-Feldspar IRSL dating of a Pleistocene river terrace staircase sequence of the Lower Tejo River (Portugal, western Iberia) - Cunha, Pedro P. (2010)
We present the results of K-feldspar IRSL dating of the four lower terraces (T3–T6) of the Portuguese Tejo River, in the Arripiado-Chamusca area. Terrace correlation was based upon: a) analysis of aerial photographs, geomorphological mapping and field topographic survey; b) sedimentology of the deposits; and c) luminescence dating. Sediment sampled for luminescence dating gave unusually high dose rates, of between 3.4 and 6.2 Gy/ka and, as a result, quartz OSL was often found to be in saturation. We therefore used the IRSL signal from K-feldspar as the principal luminescence technique. The K-feldspar age results support sometimes complex geomorphic correlations, as fluvial terraces have been vertically displaced by faults (known from previous studies). Integration of these new ages with those obtained previously in the more upstream reaches of the Tejo River in Portugal indicates that the corrected K-feldspar IRSL ages are stratigraphically and geomorphologically consistent over a distance of 120 km along the Tejo valley. However, we are sceptical of the accuracy of the K-feldspar ages of samples from the T3 and T4 terraces (with uncorrected De values >500 Gy). In these cases the Dose Rate Correction (DRC) model puts the natural signals close to luminescence saturation, giving a minimum corrected De of about 1000 Gy, and thus minimum terrace ages; this may even be true for those doses >200 Gy. Luminescence dating results suggest that: T3 is older than 300 ka, probably ca. 420–360 ka (wMarine Isotope Stage [MIS]11); T4 is ca. 340–150 ka (wMIS9-6); T5 is 136–75 ka (wMIS5); T6 is 60–30 ka (MIS3); an aeolian sand unit that blankets T6 and some of the older terraces is 30– 12 ka. Collectively, the luminescence ages seem to indicate that regional river downcutting events may be coincident with periods of low sea level (associated, respectively, with the MIS10, MIS6, MIS4 and MIS2).